2006
DOI: 10.1007/s10072-006-0521-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cavernomas and seizures: a retrospective study on 163 patients who underwent pure lesionectomy

Abstract: The objective was to evaluate the outcome of microsurgical "pure" lesionectomy in patients with supratentorial cavernous angiomas presenting with seizures. For this retrospective study 163 patients with cavernoma-related epileptic seizures were selected. They all underwent surgery in a single institution between 1988 and 2003. A microsurgical frame/frameless guided minimally invasive transulcal "pure" lesionectomy was performed. The haemosiderin stained gliotic brain parenchyma that was usually found surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 24 publications
1
94
2
4
Order By: Relevance
“…The early surgical removal of superficial or not critically located CMs causing seizures may offer real curative treatment of epilepsy, preventing psychosocial disability in patients on long-term medical therapy and avoiding the risk of neurological deficits from growth and hemorrhage of the cavernomas [169, 170]. Surgery may also improve the efficiency of anticonvulsant therapy in patients with epilepsy who are resistant to medication [171,172,173]. Removal of the malformation through a simple lesionectomy may obtain good results for seizure outcome when there is concordance between the site of the epileptogenic cavernoma, the clinical semeiology and the interictal EEG [13,172,173,174,175,176].…”
Section: Resultsmentioning
confidence: 99%
“…The early surgical removal of superficial or not critically located CMs causing seizures may offer real curative treatment of epilepsy, preventing psychosocial disability in patients on long-term medical therapy and avoiding the risk of neurological deficits from growth and hemorrhage of the cavernomas [169, 170]. Surgery may also improve the efficiency of anticonvulsant therapy in patients with epilepsy who are resistant to medication [171,172,173]. Removal of the malformation through a simple lesionectomy may obtain good results for seizure outcome when there is concordance between the site of the epileptogenic cavernoma, the clinical semeiology and the interictal EEG [13,172,173,174,175,176].…”
Section: Resultsmentioning
confidence: 99%
“…Ferroli et al [3] reported that 68/99 patients that presented with epilepsy were completely seizure free after pure lesionectomy alone. On the contrary, Hammen et al [4] reported that complete resection of hemosiderin fringe surrounding the cavernoma was correlated to less post-operative seizure frequency.…”
Section: Dear Editormentioning
confidence: 99%
“…3,9,28,33 Fortunately, at follow-up the rate of severe permanent neurological deficits descends to 2.6%-8%. 3,4,9,10,12,15,28,32,33 Our strategy employing FN and iopMRI only led to two mild (7.7%) and one moderate (3.8%) permanent visual field deficit, while the rate of post-surgical general complications was 7.7% and severe neurological deficits did not occur at all.…”
Section: 32mentioning
confidence: 99%
“…In patients with chronic epilepsy, seizure-freedom rates after 2 years of followup drop to 62. rate of 68.7% after a mean follow-up of 48 months. 28 If the hemosiderin-stained tissue is also removed, these seizure free rates reach 53-78%. 9,11,12 However, a current meta-analysis by Englot and colleagues found no statistical difference between the rate of seizure freedom in lesionectomy alone (75%) and extended lesionectomy with additional excision of the hemosiderin rim (76%), without any data from studies including intraoperative imaging.…”
Section: Surgical Strategiesmentioning
confidence: 99%
See 1 more Smart Citation